Manual de procedimientos operativos, administrativos y logístico de la empresa Eventos y Buffet Julia - López Cortes, Harold Andrés (Universidad Antonio Nariño, 2021)
Every day the organizations of the service sector become more important for the economy of a country, due to the continuous development of SMEs that are born within the sector and that develop tourism activities, organization of events; taking advantage of new technologies and new forms of consumption. For a service company, it is of vital importance to be able to satisfy the needs of customers, offering quality services with high standards of customer service and effective and efficient logistics distribution, because through these aspects a perception of general quality of the company will be achieved. company, in addition to achieving loyalty and market recognition of the company. Therefore, in this paper, the necessary steps are presented for the elaboration of a manual of procedures for the operational, administrative and logistics area of ​​the company Eventos y Buffet Julia, all in order to improve the processes in those areas, increase the productivity and profitability of the company.